2017
DOI: 10.3892/etm.2017.5626
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of renal morphology on 3-dimensional ultrasonography with renal pathologic findings and outcome in biopsy-proven nephropathy

Abstract: Abstract. Kidney morphology has been used to estimate renal functions. The present study investigated the usefulness of kidney length and renal parenchymal volume (RPV) measured using three-dimensional ultrasonography (3-D USG) in estimating renal pathological findings, and the outcome in patients with nephropathy who underwent renal biopsy. In this study, 94 adult patients who had native kidney biopsy with 3-D USG results were included. The mean kidney length and RPV were independent factors of, and positivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
1
1
0
Order By: Relevance
“…In this study, renal length (OR: -1.62 [-2.06, -1.19]) and renal 3D volume (OR: -0.05 [-0.07, -0.03]) showed signi cant differences in severe renal injure, even after adjusting for confounding variables such as gender, age and BMI. This result indicated that renal volume and renal length were effective parameters for the assessment of severe renal injure and showed a negative correlation, which was consistent with the study by Xu et al in 2018 ( 32 Xu et al, 2018). However, in early and moderate pathological injure, the results showed that the pathological structural injure had not caused signi cant morphological changes, and the individual differences between kidneys were relatively large.…”
Section: Discussionsupporting
confidence: 90%
“…In this study, renal length (OR: -1.62 [-2.06, -1.19]) and renal 3D volume (OR: -0.05 [-0.07, -0.03]) showed signi cant differences in severe renal injure, even after adjusting for confounding variables such as gender, age and BMI. This result indicated that renal volume and renal length were effective parameters for the assessment of severe renal injure and showed a negative correlation, which was consistent with the study by Xu et al in 2018 ( 32 Xu et al, 2018). However, in early and moderate pathological injure, the results showed that the pathological structural injure had not caused signi cant morphological changes, and the individual differences between kidneys were relatively large.…”
Section: Discussionsupporting
confidence: 90%
“…Three-dimensional US is a promising technique for renal volume assessment (31). Recent data suggest that morphological kidney parameters provided by 3D US might be more accurate than 2D US (32). However, this technique is not yet established in routine clinical practice.…”
Section: Discussionmentioning
confidence: 99%